Analisis Indeks Massa Tubuh Dan Tekanan Darah Mahasiswa Kedokteran: Implikasi Untuk Pencegahan Hipertensi Dini - Farid Bastian; Satria Safirza; Elmiyati Elmiyati; Ratih Ayu Atika; Syarifah Nora Andriyati (Lembaga Teewan Journal Solutions, 2026)
Hypertension is one of the non-communicable diseases (PTM) that has become a serious health problem in recent years and is often referred to as a “silent killer” because it frequently occurs without symptoms. Hypertension is generally found in older adults; however, several studies have shown that it can also occur in adolescents, with its prevalence increasing in recent years. Many individuals are not aware that hypertension occurring during adolescence may persist into adulthood and increase the risk of morbidity and mortality. The aim of this literature review is to analyze the influence of various risk factors on the incidence of hypertension in adolescents. This study is a quantitative study with an observational approach using a cross-sectional design. The population in this study consists of students of the Faculty of Medicine, Universitas Abulyatama, particularly cohorts 2022, 2023, and 2024. The results of this study show that the characteristics of respondents are predominantly female (71%) compared to male (28.9%). Most respondents are classified as IMT Obesity I (35.22%). The distribution of blood pressure shows that the majority of respondents are in the pre-hypertension category (59.74%), followed by normal blood pressure (25.78%), hypertension stage I (11.32%), and hypertension stage II (1.25%). There is a tendency that respondents with overweight and obesity IMT are more likely to be in the pre-hypertension category, indicating a possible relationship between increased IMT and the tendency of elevated blood pressure in adolescents and young adults. This suggests that medical students are already in an early cardiovascular risk phase that has the potential to develop into hypertension if early prevention is not implemented.